If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -8 = 2x + 4 Reorder the terms: -8 + 3x = 2x + 4 Reorder the terms: -8 + 3x = 4 + 2x Solving -8 + 3x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -8 + 3x + -2x = 4 + 2x + -2x Combine like terms: 3x + -2x = 1x -8 + 1x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 -8 + 1x = 4 + 0 -8 + 1x = 4 Add '8' to each side of the equation. -8 + 8 + 1x = 4 + 8 Combine like terms: -8 + 8 = 0 0 + 1x = 4 + 8 1x = 4 + 8 Combine like terms: 4 + 8 = 12 1x = 12 Divide each side by '1'. x = 12 Simplifying x = 12
| 72(-4+4x)=64(27) | | 32=8p+24 | | 96(-4+4x)=36(27) | | 36(-4+4x)=96(27) | | 8.75+2.25x=29 | | 64(-4+4x)=72(27) | | 3x^3-x^2-9=27 | | x^4-7x^2+9=0 | | 4r+5r+41=104 | | 1.7q-1.5-2.5q=1.8q-2.3 | | 8m-7=4m+5 | | -2(c-1)=-22 | | x^3-3x^2+3=27 | | 6(y+1)=6 | | X^2+6-10=0 | | 18-n=n | | x^4-7x^2+9=27 | | 3(a-4)=33 | | 22=4+8c-2e | | 2x-6=54-4x | | 24(5x+11)=88(18) | | y-q=m(x-p) | | 5x^3y+10x^2y-40xy=0 | | 2x+3=-3x-4 | | 15x-10y=32 | | 24=5r+r*r | | 2-n=7-2n | | 11a-3a+9=-7 | | 8-2n=26 | | x+13=49 | | x^2-7x+42=0 | | 9x^3y+81x^2y-90xy=0 |